Earthquakes and dams: Remote and direct monitoring of UK earthquakes affecting dam infrastructure. Issue 4 (10th December 2021) - Hawthorn, David E.; Mosca, Ilaria; Baptie, Brian J.; Walker, Alice
Abstract : Although earthquake hazard in the UK is low, there is a long history of earthquakes that have been widely felt or in some cases caused damage. Although these events are relatively rare, earthquake hazard assessment is still required for structures, such as dams, where the consequence of failure may be very high. Since 1990 the UK has experienced more than 13 earthquakes of greater than magnitude 4. The largest recorded onshore earthquake was a 5.4 local magnitude (ML) (Lleyn Peninsula, 1984) and the largest offshore was the 6.1 ML (Dogger bank, 1931). Smaller earthquakes can also produce levels of ground motion more typically associated with larger earthquakes; for instance, if they are unusually shallow or otherwise close to a structure of interest. In this talk two different, but potentially complimentary, methods of monitoring reservoir infrastructure for the affects of earthquakes are considered: remote monitoring of a region with a rapid alert system combined with the use of ground motion prediction equations to assess the likely ground motions at facilities of interest and direct emplacement of seismic sensors in or around reservoir structures to provide absolute values of ground motion during an earthquake.